2017
DOI: 10.1080/0142159x.2017.1403014
|View full text |Cite
|
Sign up to set email alerts
|

Changes in medical student implicit attitudes following a health equity curricular intervention

Abstract: eQuality reduced implicit preference for "Straight" and "White." Differences in M1 post-intervention IAT scores between groups suggest dedicating time to debrief implicit attitudes enhances bias mitigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 43 publications
0
34
0
3
Order By: Relevance
“…We did not find an association between social contact and professional exposure to transgender people and knowledge, which may be a result of the retrospective nature of our study and the fact that we did not assess the effects of a specific, educational encounter. In addition to formal curricula to address implicit bias in medical education, many have stressed the importance of addressing informal instruction (or ‘the hidden curriculum’, including institutional culture) in medicine in order to decrease implicit bias . Interventions that address norms, such as increasing medical student diversity, experiences that promote empathy and role modelling, have been suggested specifically in caring for stigmatised populations .…”
Section: Discussionmentioning
confidence: 99%
“…We did not find an association between social contact and professional exposure to transgender people and knowledge, which may be a result of the retrospective nature of our study and the fact that we did not assess the effects of a specific, educational encounter. In addition to formal curricula to address implicit bias in medical education, many have stressed the importance of addressing informal instruction (or ‘the hidden curriculum’, including institutional culture) in medicine in order to decrease implicit bias . Interventions that address norms, such as increasing medical student diversity, experiences that promote empathy and role modelling, have been suggested specifically in caring for stigmatised populations .…”
Section: Discussionmentioning
confidence: 99%
“…Included [31,32]: Describes the innovation and outcomes of the innovation [30,34]; Components of the larger systemslevel work; [33] Formative work N/A [31] N/A [31] Yes [32] Yes [32] N/A [33] N/A [33] No [34] N o [ 34] University of Pennsylvania Perelman Schools of Medicine, Nursing, and Dentistry [2,35,36] Yes [2] N o [ 2] Individual [2] Included No [35] N/A [35] Systems [35] N/A [36] N/A [36] Systems [36] University of Pittsburg School of Medicine [37] No No Individual Included…”
Section: No Individual Includedmentioning
confidence: 99%
“…Consequently, some healthcare programmes have introduced teaching on LGBT+ health. An example of a comprehensive teaching programme is that offered by the University of Louisville School of Medicine, who have introduced a 50.5 hour integrated programme including a patient panel, with encouraging initial outcomes in terms of reduced implicit bias based on sexuality [10]. A recent systematic review of 15 LGBT+ teaching programmes (seven of which were medical schools) found improvements in knowledge, attitudes and/or practice towards LGBT+ people, however they did not evaluate whether these translated into improvements in the care of LGBT+ patients.…”
Section: Introductionmentioning
confidence: 99%